2015
DOI: 10.1002/2014jd022372
|View full text |Cite
|
Sign up to set email alerts
|

Increase in upper tropospheric and lower stratospheric aerosol levels and its potential connection with Asian pollution

Abstract: Satellite observations have shown that the Asian Summer Monsoon strongly influences the upper troposphere and lower stratosphere (UTLS) aerosol morphology through its role in the formation of the Asian Tropopause Aerosol Layer (ATAL). Stratospheric Aerosol and Gas Experiment II solar occultation and Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) lidar observations show that summertime UTLS Aerosol Optical Depth (AOD) between 13 and 18 km over Asia has increased by three times since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
303
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(330 citation statements)
references
References 38 publications
24
303
3
Order By: Relevance
“…Layer" is hypothesized to loft pollution during the Asian summer monsoon (Vernier et al, 2011;Vernier et al, 2015). Dust storms can loft dust, particularly effective ice condensation nuclei, to high enough altitudes to co-exist with ice clouds (Klein et al, 2010).…”
Section: Misclassified Cirrus Fringe Filtermentioning
confidence: 99%
“…Layer" is hypothesized to loft pollution during the Asian summer monsoon (Vernier et al, 2011;Vernier et al, 2015). Dust storms can loft dust, particularly effective ice condensation nuclei, to high enough altitudes to co-exist with ice clouds (Klein et al, 2010).…”
Section: Misclassified Cirrus Fringe Filtermentioning
confidence: 99%
“…A related phenomenon is the buildup of the Asian tropopause aerosol layer (ATAL; Vernier et al, 2011), which has recently been estimated to cause a significant regional radiative forcing of −0.1 W m −2 (Vernier et al, 2015), cooling the Earth's surface. Hence, transport in the Asian monsoon is likely an important factor for climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, another possible pathway through which meteorological covariability can influence our correlation analysis over the ISMR is due to the positive association between the magnitude of the Asian tropopause aerosol layer and AOD. However, the tropopause aerosol layer pathway results in insignificant enhancements of AOD during JJAS by ∼ 0.01-0.02 over south Asia compared to the observed climatological mean AOD (∼ 0.6) (Vernier et al, 2015;Yu et al, 2015). Thus, contributions of the Asian tropopause aerosol layer to the observed positive gradients (Fig.…”
Section: Decoupling the Role Of Meteorologymentioning
confidence: 93%
“…Ground-based remote sensing, satellite observations, aircraft measurements, and modeling studies have documented that aerosols are mainly located within the boundary layer during the monsoon period over the ISMR (Mishra and Shibata, 2012;Misra et al, 2012;Sarangi et al, 2015). But some recent studies have reported that the transport of nearsurface aerosols to the free troposphere by mesoscale convection results in upper-level accumulation during the summer monsoon, termed the Asian tropopause aerosol layer (Chakraborty et al, 2015;Vernier et al, 2015). Therefore, another possible pathway through which meteorological covariability can influence our correlation analysis over the ISMR is due to the positive association between the magnitude of the Asian tropopause aerosol layer and AOD.…”
Section: Decoupling the Role Of Meteorologymentioning
confidence: 99%